2022
DOI: 10.1021/acsapm.2c01429
|View full text |Cite
|
Sign up to set email alerts
|

Isomer-Free Quinoidal Conjugated Polymers with Different Core Lengths for Organic Field-Effect Transistors

Abstract: Quinoid platforms have garnered considerable attention as promising candidates for conjugated building blocks because of their superior charge transport properties and high electrical conductivity. Because the quinoid structure can easily adjust the optoelectronic properties by controlling the length of the quinoid core, it has the advantage of choosing the desired purpose. However, double-bond linkages within the quinoid structure could generate geometric isomers, which hinder the purification process and und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…6-Bromo-1-(2-decyltetradecyl)indoline-2,3-dione and mQEDOT-Br were synthesized using modified and previously reported procedures, respectively. 20,21,51 1 H NMR (400 MHz, CDCl 3 ) δ 7.84 (d, J = 8.4 Hz, 1H), 6.89 (d, J = 8.3 Hz, 1H), 4.63 (s, 2H), 3.44 (d, J = 7.1 Hz, 2H), 1.73 (s, 1H), 1.24 (s, 40H), 0.87 (t, J = 6.3 Hz, 6H).…”
Section: Methodsmentioning
confidence: 99%
“…6-Bromo-1-(2-decyltetradecyl)indoline-2,3-dione and mQEDOT-Br were synthesized using modified and previously reported procedures, respectively. 20,21,51 1 H NMR (400 MHz, CDCl 3 ) δ 7.84 (d, J = 8.4 Hz, 1H), 6.89 (d, J = 8.3 Hz, 1H), 4.63 (s, 2H), 3.44 (d, J = 7.1 Hz, 2H), 1.73 (s, 1H), 1.24 (s, 40H), 0.87 (t, J = 6.3 Hz, 6H).…”
Section: Methodsmentioning
confidence: 99%
“…Using a similar strategy, O⋯S non-covalent interactions and steric repulsion were employed towards the synthesis of bis-QEDOT, compound 17 [ 53 ]. Similarly, Kim et al found that compound 17 and 18 were synthesized simultaneously by the indophenine reaction under sulfuric acid catalytic conditions with yields of 40% and 12%, respectively [ 54 ]. Both quinoid monomers were confirmed to have a single geometric structure with NMR analysis, which also confirms the intramolecular nonbonding S···O interactions.…”
Section: Synthetic Tactics Of π-Extended Quinoidal Acceptorsmentioning
confidence: 99%
“…In addition, several isatin-terminated quinoidal bithiophene (QuBT) derivatives have been developed by modifying thiophene moieties between isatin rings, such as fused thiophene rings, 3,4-dimethoxythiophene (DMOT), 3,4-ethylenedioxythiophene (EDOT), and 3,4-propylenedioxythiophene (ProDOT), entailing the suppression of geometrical isomers (Figure ). Such synthetic versatility allows for the development of several QCPs as well as small molecules, which have been applied to unipolar or ambipolar organic field-effect transistors (OFETs) as active materials. …”
Section: Introductionmentioning
confidence: 99%